Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.

Influence of surface hydrophobicity on the esterification of fatty acids over solid catalysts - Satyarthi, Jitendra K.; Srinivas, Darbha; Ratnasamy, Paul (Energy & Fuels, 2010)
The relative roles of surface acidity and hydrophobicity in the methylation of fatty acids (C(8) - C(18)) to the corresponding methyl esters were investigated over three solid acid catalysts: Fe-Zn double-metal cyanide (DMC), sulfated zirconia (SZ), and Al-MCM-41. The esterification reaction was faster and the apparent activation energy was lower over SZ and Al-MCM-41 than on DMC because of their higher acid strength, specific surface area, and pore diameter. Over SZ and Al-MCM-41, the apparent activation energy for esterification increased with the chain length of the fatty acid. A reverse trend, however, was observed over DMC. The relative adsorption of methanol and fatty acids (compared to water) was higher on DMC than on SZ and Al-MCM-41. Hence, in addition to the acidic and textural properties, surface hydrophobicity and relative surface coverage by reactants/products also play an important role in reactions of long-chain fatty acids with alcohols on solid catalysts.

Biodiesel production from vegetable oils and animal fat over solid acid double-metal cyanide catalysts - Srinivas, Darbha; Satyarthi, Jitendra K. (Catalysis Surveys from Asia, 2011)
Biodiesel comprises of fatty acid alkyl esters prepared from vegetable oils or animal fat by esterification/transesterification with short-chain alcohols (methanol or ethanol, for example). It is a biodegradable renewable fuel. Its production is growing exponentially due to greater concerns about environmental protection and depletion of fossil fuel resources. Further, its production from non-edible oils and animal fat is more desirable than from edible oils due to lower cost of non-edible feedstocks and elimination of food verses fuel issues. Solid acid catalysts are ideal for conversion of such low-grade oils to biodiesel. Biodiesel from non-edible oils can be produced by two methods: (1) simultaneous esterification of fatty acids and transesterification of fatty acid glycerides and (2) hydrolysis of glycerides followed by esterification. This account reports the catalytic performance of solid, Fe-Zn double-metal cyanide (DMC) complexes and other acid catalysts in these transformations for biodiesel production. The factors influencing the catalytic performance of the solid acid catalysts in biodiesel production are discussed.
Keywords: Biodiesel; Double-metal cyanide; Esterification; Hydrolysis; solid acid catalysts; transesterification

Fourier transform infrared spectroscopic method for monitoring hydroprocessing of vegetable oils to produce hydrocarbon-based biofuel - Satyarthi, Jitendra K.; Srinivas, Darbha (Energy & Fuels, 2011)
A novel Fourier transform infrared spectroscopic method is reported, for the first time, to estimate the conversion of vegetable oil (soybean oil, for example) to hydrocarbon-based biofuel via hydroprocessing. The infrared peak attributed to the carboxyl group (O-C=O) is used as a marker to determine the conversion of fatty acid glycerides in soybean oil to hydrocarbons. Unlike the conventional gas chromatographic method, this new method of estimation is fast and requires no derivatization of the sample and predetermination of response factors of each chemical component in vegetable oil/product samples. H-1 and C-13 nuclear magnetic resonance spectroscopy techniques are also reported to substantiate and confirm the purity and product formation in the hydroprocessing reaction.

Lanthanum and zinc incorporated hydrotalcites as solid base catalysts for biodiesel and biolubricants production - Rahul, R.; Satyarthi, Jitendra K.; Srinivas, D. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
Mg-Al hydrotalcites doped with varying amounts of lanthanum and zinc ions (10 30 mol %) have been prepared by co-precipitation method and used, after calcination at 873 K, as solid base catalysts for transesterification of soybean oil with methanol (producing biodiesel) and n-octanol (producing biolubricants). The catalyst with 20 mol % of lanthanum shows the highest transesterification activity (soybean oil conversion = 100 % and biodiesel yield = 95 %) at 423 K in 4 h. Catalytic activity varies in proportion with the basicity of the catalysts.
Keywords: Biodiesel; Biolubricants; catalysis; Doped hydrotalcites; Hydrotalcites; Lanthanum; Solid base catalysts; transesterification; Vegetable oils; zinc

Selective epoxidation of methyl soyate over alumina-supported group VI metal oxide catalysts - Satyarthi, Jitendra K.; Srinivas, D. (Applied Catalysis A-General, 2011)
Epoxidation of methyl soyate (biodiesel), soybean oil and oleic acid with tert.-butyl hydroperoxide (TBHP) was investigated over gamma-alumina-supported group VI metal oxides (CrOx/Al2O3, MoOx/Al2O3 and WOx/Al2O3) prepared by impregnation method. The studies revealed that 15 wt% MoOx on gamma-Al2O3 was the most active catalyst (conversion >90 mol% under optimized conditions). While MoOx/Al2O3 is selective mainly for epoxidation, the other catalysts are active for epoxidation as well as for decomposition of TBHP. The active species on the catalyst surface were investigated using in situ UV-visible spectroscopy. A linear correlation was observed between epoxidation activity and surface acidity of the catalyst. A new H-1 NMR method was developed to monitor the progress of epoxidation reaction which was found to be superior to gas chromatographic method in estimating the conversion of double bonds of fatty compounds. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Alumina-supported group VI metal oxides; Biodiesel; epoxidation; Fatty acids; H-1 NMR spectroscopy; MoOx/Al2O3; Vegetable oil